Feedback workshops from Crimean-Congo haemorrhagic fever study and assessment of One Health implementation in rural communities of Burkina Faso - Ilboudo, Abdoul K.; Ilboudo, Guy S.; Dione, Michel M.; Bett, Bernard K. (International Livestock Research Institute, 2025)
This is a report of two feedback workshops held on 16 and 20 December 2024 in the North and Hauts-Bassins regions of Burkina Faso by the One Health Research, Education and Outreach Centre in Africa (OHRECA), which is led by the International Livestock Research Institute (ILRI). These workshops came after the completion of a study on the epidemiology of Crimean-Congo haemorragic fever (CCHF) conducted in January–March 2023 in the two regions of the country.